A Critique of the Agency Theory Viewpoint of Stock Price Crash Risk: The Opacity and Overinvestment Channels - Andreou, Panayiotis; Lambertides, Neophytos; Magidou, Marina (My University, 2022)
This study documents a puzzling historical trend in crash risk for US-listed firms: between 1950 and 2019, the firm-year occurrences of idiosyncratic stock price crashes rose from 5.5% to an astonishing 27%. The vastness of the literature notoriously attributes crashes to agency reasons, i.e. self-interested executives who strategically camouflage bad news via the financial reporting opacity and overinvestment channels. Nonetheless, we document that the opacity– and overinvestment–crash relations are non-significant, especially in the period following the enforcement of the Sarbanes–Oxley Act. The statistically non-significant relations are also witnessed in tests that account for the effect of equity-based compensation incentives and corporate governance functions. Overall, this study criticizes the efficacy of opacity and overinvestment as channels in explaining crash risk. Our conclusions offer avenues for future research to pursue in rationalizing the puzzling surge in stock price crashes.
Keywords: Stock Price Crash Risk; Opacity; Overinvestment; Channels